Effects of inter-wire arc posture on cross-coupling arc characteristics. (April 2020) - Dong, Shanwen; Chen, Shujun; Jiang, Fan; Xu, Bin; Yuan, Chengwei; Lu, Zhenyang
Abstract: Cross-coupling arc (CCA) forces two arcs to cross-couple in a limited space, and is able to decouple heat tranfer, force transfer and mass transfer in the welding process. However, the main arc deflects regularly to the cathode of the inter-wire arc (IWA) (called polar zone phenomena), affecting the CCA stability. To reduce the degree of polar zone phenomena on the CCA, a method to adjust the IWA posture was proposed, and the effects of the IWA posture on the CCA characteristics were investigated. A synchronized acquisition system with high-speed camera and electric signal was adopted during the experiment. The results showed that adjusting the IWA posture is feasible and effective to reduce the effects of polar zone phenomena, and increasing the current angle of the IWA contributes to reducing the deflection of main arc. Increasing the height of the cathode wire is an effective way to reduce the deflection of main arc, and reasonably increasing the interval of wires is able to reduce the deflection of main arc. Both methods have more effect on the IWA current and the main arc voltage than changing the wire angles. Increasing the anode-cathode wire angles has little effect on the deflection of main arc, but only increasing the anode wire angle could increase or decrease the deflection of main arc. Both methods have smaller effect on the IWA current and the main arc voltage than changing the height of the wires.